Profile of Carbapenem Resistant Gram Negative Bacilli in Grha Kedoya Hospital Jakarta - Venny Patricia; Ahmad Yani; Etik Sutarti (Jurnal teknologi Kesehatan Borneo, 2023)
Carbapenems are beta-lactam antibiotics included in the 3rd line of antibiotics, which are the last choice in therapy to overcome various bacterial infections. The more use of antibiotics that are not in accordance with the clinical situation, the more cases of carbapenem resistance found in the hospital. This study aims to analyze gram-negative bacteria, which are resistant to carbapenem antibiotics, in Grha Kedoya Hospital from January to March 2022 using an observational analytical research design for bacterial identification and antibiotic sensitivity testing using colorimetric and turbidimetric methods with a cross-sectional research design. The examination material was all samples infected with Gram-negative bacteria, as many as 174 samples. The data analysis used in this study was descriptive crosstabs. The results stated that there were carbapenem-resistant bacteria in as many as 32 samples (18.4%); the most carbapenem-resistant bacteria were Acinetobacter baumannii bacteria in as many as 16 patients (50%); Pseudomonas aeruginosa and Klebsiella pneumoniae in as many as 8 patients (25%); and the resistance test showed 100% resistance to the antibiotics Doripenem, Imipenem, Meropenem, and Ertapenem.